1982
DOI: 10.3758/bf03327003
|View full text |Cite
|
Sign up to set email alerts
|

The paleocerebellum and the integration of behavioral function

Abstract: The role of the cerebellum in motor function is well documented. Additional data clearly im· plicate the cerebellum in the regulation of sensory processes and autonomic functions, and more recent findings establish an influence of cerebellar systems on the regulation of emotional and motivational behaviors. The cerebellum provides extensive projections to brain· stem and limbic mechanisms that have been implicated in behavioral regulation, and experimen· tal manipulations of the cerebellum have been found to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 104 publications
6
33
0
Order By: Relevance
“…These results have been confirmed in rats (Heath et al, 1978) and monkeys (Heath and Harper, 1974). In addition, the vermis by way of fastigial nucleus projects (i) to periaqueductal gray area, a region that has anatomical bidirectional connections with amygdala and septum and (ii) to the locus coeruleus and the ventral tegmental area, the centers of catecholaminergic systems (Berntson and Torello, 1982). Therefore, given its anatomical and functional connections with several structures involved either in somatosensory perception (as the brainstem, thalamus), in emotional state (amygdala, septum and locus coeruleus) and in the control of motor responses, the vermis may represent an interface between the sensory stimuli, the emotional state of the subject and the motor responses.…”
Section: Neural Basis Of the Cerebellar Involvement In Learned Fearsupporting
confidence: 65%
See 2 more Smart Citations
“…These results have been confirmed in rats (Heath et al, 1978) and monkeys (Heath and Harper, 1974). In addition, the vermis by way of fastigial nucleus projects (i) to periaqueductal gray area, a region that has anatomical bidirectional connections with amygdala and septum and (ii) to the locus coeruleus and the ventral tegmental area, the centers of catecholaminergic systems (Berntson and Torello, 1982). Therefore, given its anatomical and functional connections with several structures involved either in somatosensory perception (as the brainstem, thalamus), in emotional state (amygdala, septum and locus coeruleus) and in the control of motor responses, the vermis may represent an interface between the sensory stimuli, the emotional state of the subject and the motor responses.…”
Section: Neural Basis Of the Cerebellar Involvement In Learned Fearsupporting
confidence: 65%
“…Removal of the cerebellum was shown to impair performance of salivary, cardiac, and respiratory conditioning (Berntson andTorello 1982 andSacchetti et al 2005). These effects on aversive conditioning can be localized to the cerebellar vermis.…”
Section: Cerebellar Vermis and Fear Conditioning In Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence that the cerebellum of mammals is also involved in emotional behaviors as part of an integrated network that regulates fear responses (3,4). Moreover, it has been reported that the cerebellar vermis is connected to several limbic areas and is involved in emotional learning, for example active avoidance (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Although little is known about the emotional behaviors of non-mammals, neuroanatomical studies have revealed that the neuronal organization, basic circuitry and neurophysiologic characteristics of the cerebellum of teleost fish are similar to those of the mammalian cerebellum (6,7). Also, teleosts are suitable for studies with histamine because the central histaminergic system of fish has only one area of projection to the telencephalon (8,9).…”
Section: Introductionmentioning
confidence: 99%